Diagnóstico da deficiência de fósforo em bovinos pelos exames histológicos e microrradiográficos de costelas - Pilati, Célso; Dutra, Iveraldo S. [UNESP]; Behrens, Konrad; Döbereiner, Jürgen; Dämmrich, Klaus (My University, 1996)
The objective of the present study was to show the efficiency of histologic and microradiographic techniques performed on rib bone samples as a mean of diagnosing the phosphorus status of cattle raised on phosphorus deficient pastures and receiving different mineral supplements. The rib samples were obtained from cattle of different ages which died from disease that was clinically and epidemiologically diagnosed as botulism. Ten out of 24 juvenile and adult animals studied exibited alterations of osteomalacia, while the others without those alterations served as controls. It is suggested that the method could be useful to improve the diagnosis of phosphorus deficiency of cattle in Brazil.
Diagnosis of phosphorus deficiency in cattle by histologic and microradiographic examination of ribs
Keywords: Cattle; Diagnosis; Histologic and microradiographic examination; Phosphorus deficiency; Rib bone